2020
DOI: 10.1039/d0ee01039a
|View full text |Cite
|
Sign up to set email alerts
|

Environmental impacts of III–V/silicon photovoltaics: life cycle assessment and guidance for sustainable manufacturing

Abstract: By requiring less materials, multijunction III–V/silicon photovoltaic cells may further reduce the life cycle environmental impacts of solar PV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…Life-cycle analyses have shown that the III-V//Si technology has the potential to be comparable or even superior in environmental impact compared to single-junction silicon solar cells of today. 42 From comparing this cell to the currently best triple-junction device, we found that despite the nonoptimum bandgap combination, the silicon-based cell compares well with the best-in-class device in terms of voltage even after the different bandgaps are considered.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Life-cycle analyses have shown that the III-V//Si technology has the potential to be comparable or even superior in environmental impact compared to single-junction silicon solar cells of today. 42 From comparing this cell to the currently best triple-junction device, we found that despite the nonoptimum bandgap combination, the silicon-based cell compares well with the best-in-class device in terms of voltage even after the different bandgaps are considered.…”
Section: Discussionmentioning
confidence: 90%
“…If the costs can be reduced in the future, the presented results may therefore increase the market entrance chances for III–V//Si solar cells. Life‐cycle analyses have shown that the III–V//Si technology has the potential to be comparable or even superior in environmental impact compared to single‐junction silicon solar cells of today 42 …”
Section: Discussionmentioning
confidence: 99%
“…Finally, the reduced overpotentials from catalysis and ion transport offer the opportunity to use emerging solar cell material configurations such as III-V/Si tandem configurations, where the challenges of internal interfaces reduce the effective photovoltage. 20 These considerations are highly relevant for the design and commercialisation of highly efficient thermally coupled solar water splitting, which could use III-V/Si 21 or Perovskite/Si 33 tandem cells in a wired design or with the absorber fully immersed in the electrolyte. Some scientific and engineering challenges remain.…”
Section: View Article Onlinementioning
confidence: 99%
“…Similar to III-V solar cells for space applications, 10 costs of the absorber are, however, probably not a major issue for niche-applications in remote world regions, where the approach competes with the supply of conventional fuels that is associated with great expense and effort. As soon as the technology is established, costs can benefit from scale-up as well as from emerging low-cost, highefficiency approaches 20,21 that would extend the commercial use case beyond just niche also into regions with better infrastructure. Such a development path from the niche to larger markets has already occurred for high-efficiency photovoltaics, which reached maturity in space applications.…”
mentioning
confidence: 99%
“…7,21 In the PV community, such multi-junction solar cells based on Si bottom absorbers are currently being investigated with the aim to end the dominance of single-junction Si solar cells in the PV market. 4 Wide-bandgap III/V-semiconductors 6 or perovskites 1,14 are considered as potentially economically viable candidates to be used as top absorbers. In addition, all-perovskite multi-junctions are also regarded as promising material combinations.…”
Section: Introductionmentioning
confidence: 99%